A phase II study of pomalidomide, daily oral cyclophosphamide, and dexamethasone in relapsed/refractory multiple myeloma. Issue 9 (28th July 2020) - Van Oekelen, Oliver; Parekh, Samir; Cho, Hearn J.; Vishnuvardhan, Nivetha; Madduri, Deepu; Richter, Joshua; Ip, Chun; Lau, Kenneth; Florendo, Erika; Mancia, Ines S.; Thomas, Joanne; Verina, Daniel; et al.
Abstract: Relapsed/refractory multiple myeloma patients treated with pomalidomide and dexamethasone have an overall response rate (ORR) of ∼30% and median progression-free survival (PFS) of 4–5 months. Previous studies explored addition of weekly cyclophosphamide, but we hypothesized that daily dosing allows for better synergy. We report the open-label, single-center phase II study of pomalidomide, daily cyclophosphamide and weekly dexamethasone (PCD). Thirty-three patients were evaluable for efficacy and underwent 28-day cycles of pomalidomide (4 mg/day, D1-21), cyclophosphamide (50 mg b.i.d., D1-21) and weekly dexamethasone. All were lenalidomide-refractory and 55% were refractory to lenalidomide and proteasome inhibitor. ORR was 73%; median PFS and overall survival were 13.3 months and 57.2 months respectively. Grade 3/4 toxicities were primarily hematologic but manageable with dose reductions. Early disease progression correlated with MYC expression and flow cytometry demonstrates an activated microenvironment post-PCD. Addition of metronomic cyclophosphamide to pomalidomide and dexamethasone is a cost-effective, oral regimen with encouraging PFS.